“Double Bind” with a twist: A corpus-assisted discourse study of gender performances of male and female entrepreneurs on Twitter (now X) - Ming Liu; Guofeng Wang; Ruinan Zhao (PLoS ONE, 2025)
Previous studies have demonstrated that women in male-dominated fields face a challenging “double bind”—they must display traditionally masculine traits while maintaining feminine qualities. This study provides a corpus-assisted discourse analysis of gender performances by male and female entrepreneurs on Twitter (now X) at three levels: (1) issues, (2) personality traits, and (3) linguistic styles. The primary purpose is to examine how the “double bind” manifests in male and female entrepreneurs’ social media performances. The findings suggest that both male and female entrepreneurs strategically navigate the “double bind”, balancing gender role expectations while engaging their followers across diverse topics. Their performances feature a “double bind” with a twist, as both male and female entrepreneurs tend to adopt an interactive and engaging style rather than a combative and confrontational one to connect with their followers and maintain interactive intimacy.